2019
DOI: 10.1080/02670844.2019.1668677
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural investigations of 800 keV Ar ions irradiated nanocrystalline ZrN thin films

Abstract: The effect of 800 keV Ar ion irradiation on the microstructure and composition of ZrN films grown by pulsed laser deposition technique was investigated. Grazing incidence and symmetrical X-ray diffraction showed films were nanostructured, with grain size around 13 nm and (111) textured. X-ray reflectivity investigations showed a 0.7% decrease of films density after irradiation with a fluence of 1 × 10 14 cm −2 and no further decreased for a fluence of 1 × 10 15 cm −2 . An increase of the lattice parameter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…XPS was used to analyze the composition of the modified layers, and the split-peak fitting was carried out. All of the spectroscopies were corrected with a 284.6 eV peak of the C element, as was performed in other works about ZrN [12,34,35,42]. Figure 4a-c present the Zr3d high resolution XPS of the samples prepared at 0.4 A/100 min, 0.6 A/60 min and 0.8 A/60 min, respectively.…”
Section: Phase Composition and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…XPS was used to analyze the composition of the modified layers, and the split-peak fitting was carried out. All of the spectroscopies were corrected with a 284.6 eV peak of the C element, as was performed in other works about ZrN [12,34,35,42]. Figure 4a-c present the Zr3d high resolution XPS of the samples prepared at 0.4 A/100 min, 0.6 A/60 min and 0.8 A/60 min, respectively.…”
Section: Phase Composition and Microstructurementioning
confidence: 99%
“…Compared with TiN and other metal nitrides, ZrN shows better mechanical and frictional properties and oxidation resistance [9,10]. Of course, nanocrystalline ZrN film is also considered as an ATF coating due to its high irradiation resistance [11,12]. The preparation of ZrN coatings with compact structure and excellent interface bonding strength is essential to protect the zirconium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…It also houses a dual beam charge neutralisation setup using a low energy electron beam and ion beam (ULVAC-PHI) and a connected magnetron sputtering deposition system (Chemitronics) for in situ characterisation. [120][121][122] One of the most recent additions to the family of Cr Kα-based HAXPES systems has been constructed and commissioned at Temple University (USA). The heart of the system is a custom-built high-flux monochromated 5.4 keV hard X-ray microfocus source, consisting of a 30 kV focused electron gun (Kimball Physics), a water-cooled thin-film Cr anode, and a large bent-crystal Ge (411) monochromator in a 730 mm Rowland circle geometry.…”
Section: Specs Systems Four Specs-based Haxpes Systems Are In Operation Inmentioning
confidence: 99%
“…Kochi University of Technology, Japan, has a double x-ray source laboratory HAXPES system, which combines monochromated Cr Kα and Al Kα x-ray sources from ULVAC-PHI with a Scienta Omicron EW4000 analyser. It also houses a dual beam charge neutralisation setup using a low energy electron beam and ion beam (ULVAC-PHI) and a connected magnetron sputtering deposition system (Chemitronics) for in situ characterisation [120][121][122].…”
Section: Custom Systemsmentioning
confidence: 99%
“…In recent years, nanocrystalline (NC) materials have attracted widespread attention due to their excellent mechanical [1][2][3][4][5][6][7], electrical [8,9], magnetic [9,10], and radiation tolerance [7,11] properties. Experimental results have demonstrated that NC materials can be produced by equal-channel angular pressing [12], high-pressure torsion [13,14], mechanical alloying [15][16][17], and nanoindentation [18].…”
Section: Introductionmentioning
confidence: 99%